2019
DOI: 10.5812/jjhs.85814
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Physical and Microbial Properties of Traditional Fruit Leathers in Tehran

Abstract: Background: Fruit leathers are nutritional products that are made by dehydrating a thin layer of fruit puree or juice under specific conditions, to obtain a chewy snack. Usually, the sun drying system is used to make traditional leathers, consequently takes a relatively long time and infections may occur during this period. Objectives: The aim of this work was to assess the chemical and microbial quality of traditional fruit leathers. Methods: In this study, 30 traditional sample leathers were obtained from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…This value offers a margin of safety for the storage of acid foods. As well, Roos (1995) who found that it would not only inhibit the growth of pathogenic microorganisms, on the other hand, it would strongly inhibit the growth of nonpathogenic yeasts and fungi. However, for this level of water activity, rates of non-enzymatic browning and enzymatic activity are not negligible and may even be considerable.…”
Section: Texture Profile Analysis Of Carrot-tamarind Leather Samplesmentioning
confidence: 89%
“…This value offers a margin of safety for the storage of acid foods. As well, Roos (1995) who found that it would not only inhibit the growth of pathogenic microorganisms, on the other hand, it would strongly inhibit the growth of nonpathogenic yeasts and fungi. However, for this level of water activity, rates of non-enzymatic browning and enzymatic activity are not negligible and may even be considerable.…”
Section: Texture Profile Analysis Of Carrot-tamarind Leather Samplesmentioning
confidence: 89%
“…LPE1-FB exhibited a steady TMAB increase till Day 90, followed by a small decline (3.00 log cfu/g) up to 120 days. Previously, Safaei et al (2019) reported TMAB counts (cfu/g) in plum (10-3× 10 2 ), kiwi (10-3× 10 2 ), cherry (10-3 × 10 2 ), pomegranate (<10-4 × 10 1 ), apple (10 -1.2 × 10 1 ), apricot (1.4 × 10-4 × 10 1 ), and plum/apple (<10-10 1 ) fruit leathers, consistent with our findings. However, our results were considerably lower than those reported for durian leather in various packaging materials during 12-week storage (16.57-50.53 cfu/g) by Irwandi et al (1998).…”
Section: Tmab Countsmentioning
confidence: 99%
“…The TYM counts (cfu/g) for plum (10-2.9× 10 2 ), kiwi (3 × 10-3.1 × 10 2 ), cherry (<10 −4 × 10 2 ), pomegranate (<10 −2 × 10 1 ), apple (1 × 10 2 -1.3 × 10 2 ), apricot (<10), and plum/apple (10-1.4× 10 1 ) fruit leathers were specified by Safaei et al (2019). Moreover, both Jeebit Singh et al (2020) and Irwandi et al (1998) reported that when a w level was lower than 0.6, most of the microorganisms can hardly survive.…”
Section: Tym Countsmentioning
confidence: 99%
“…Nilai pH dan kadar air yang rendah dalam bahan pangan dapat menghambat pertumbuhan bakteri dan memperpanjang umur simpan bahan pangan (Safaei et al, 2019). Berdasarkan Tabel 3. dapat dilihat bahwa nilai pH fruit leather nanas hanya dipengaruhi oleh penambahan pegagan.…”
Section: Nilai Ph Fruit Leather Nanasunclassified